Comparative efficacy, acceptability, and tolerability of lisdexamfetamine in child and adolescent ADHD: A meta-analysis of randomized, controlled trials - Maneeton B. (Dove Medical Press Ltd., 2015)
© 2015 Tomatsu et al. Background: Several studies have shown that lisdexamfetamine (LDX) is efficacious in children and adolescents with attention-deficit/hyperactivity disorder (ADHD). Objectives: Aims of this study were to systematically review the efficacy, acceptability, and tolerability of LDX in child and adolescent ADHD. Any randomized controlled trials (RCTs) of LDX versus placebo carried out in children and adolescents with ADHD were included. Data sources: The searches of the SCOPUS, MEDLINE, CINAHL and Cochrane Controlled Trials Register were performed in September 2014. Additional searches in the ClinicalTrials.gov and EU Clinical Trials Register database were conducted. Study eligibility criteria, participants, and interventions: This review included all RCTs of LDX versus placebo which were carried out in children and adolescents up to 18 years old. Additionally, the included studies must have reported the final outcomes of: i) severity of ADHD symptoms with standardized scales, ii) rates of improvement, iii) rates of discontinuation. To be more thorough, the languages of such RCTs were not limited. Study appraisal and synthesis methods: The abstracts from databases were inspected and the full text versions of relevant trials were examined and extracted for important outcomes. The efficacious measurements included either the pooled mean end-point or changed scores of ADHD rating scales, and the rate of improvement. Acceptability and tolerability were measured by the pooled overall discontinuation rate and the pooled discontinuation rate due to adverse events, respectively. A random effect model technique was utilized to synthesize the mean differences (either standardized mean differences or weighted mean differences) and relative risks (RRs) with 95% confidence intervals (CIs). Results: A total of 1,016 children and adolescents with ADHD were included. The dosage of LDX was 30 to 70 mg/day. The pooled mean change scores of LDX-treated group was significantly greater than that of the placebo (weighted mean difference [95% CI] of –15.20 [–19.95, –10.46], I2=94%). The pooled improvement rate of the LDX-treated group was also significantly higher than that of the placebo (RR [95% CI] of 0.34 [0.24, 0.47], I2=80%). The pooled overall discontinuation rate between the two groups was not significantly different (RR [95% CI] of 0.78 [0.46, 1.31], I2=63%). Similarly, the pooled discontinuation rate due to adverse events between the two groups showed no significant difference (RR [95% CI] of 1.99 [0.70, 5.64], I2=0%). Limitations: The number of included studies was limited (five RCTs). Conclusion: According to the present review, LDX was effective and well-tolerated in the treatment of child and adolescent ADHD. Unfortunately, the acceptability of LDX was not better than the placebo. Since the number of included studies was limited, the outcome from this review should be carefully interpreted and considered as preliminary. Further studies, therefore, should be conducted to confirm these findings. Implication of key findings: Lisdexamfetamine is an efficacious stimulant for treating child and adolescent ADHD.